Optimism in Vocational High School Students Through Self-Esteem and Proactive Personality - Shafira, Dona Alloydya; Priyatama, Aditya Nanda (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Indonesia’s employment data reveals a significant disparity between the unemployment rate, which is largely dominated by vocational high school (SMK) graduates, and the institution’s aim of preparing work-ready graduates. This is due to a mismatch between student’s interest and their chosen fields of study also industry demands. SMK students require optimism to face these challenges by fostering a more positive outlook on their future. Optimism is influenced by various factors, including self-esteem and proactive personality. This study aims to explore the relationship between self-esteem, proactive personality, and optimism among 202 twelfth-grade SMK students. This research employs a quantitative approach using multiple correlation analysis as the primary method, supported by partial correlation analysis and a two-sample t-test. The results indicate a significant and positive relationship between self-esteem, proactive personality, and optimism (r = 0.241; p < 0.05). This research provides a reference for understanding factors influencing optimism, particularly among SMK students. Keywords: Optimism; Proactive Personality; Self-esteem; Vocational High School Students.